Transformation Of Blood Learning Through Applications And Teaching Effectiveness Of Students In The 2019 Corona Virus Disease Pandemic Period (Covid-19) - Atmaja, Jessy Parmawati; Rostati, Rostati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The 2019 corona virus disease (Covid-19) outbreak which has hit the world, presents its own challenges for educational institutions, especially elementary schools. Through the Ministry of Education and Culture, the Government has prohibited educational institutions from implementing face-to-face (conventional) learning and ordered to organize online learning. The implementation of this system automatically encourages education actors to be ready for implementation, even though so far several schools have never conducted learning with an online system. Through this research, the researcher wants to analyze how effective the learning system is from the point of view of the educator. The sample of this research is teaching staff at the elementary school level. The instrument used was a questionnaire distributed online using the ms.form link. Online learning that is not properly prepared will have an impact on the effectiveness of teaching by educators, as well as the acceptance of students for online learning because of the very diverse abilities of acceptance of the material and delivery of educators.